EFFECT OF CITRIT ACID AND PACKAGING TYPE ON QUALITY CHANGE OF KALAMANSI JUICE DURING ROOM TEMPERATURE STORAGE - Muhammad Abdul Ratam Ikhsan; Yessy Rosalina; Lail Susanti (Jurnal Agroindustri, 2019)
Packaging  kalamansi juice  is one of the diversified alternatives to processed Kalamansi fruit.  Purpose of this study was to obtain a method of processing Kalamansi juice in a bottle packaging. This study was conducted following  factorial Randomized Completely Design. The first treatment factor was the use of citric acid, which consists of four concentration levels, namely: 0 g / L (A1), 0.5 g / L (A2), 1 g / L (A3) and 1.5 g / L (A4 ). The second treatment factor was the use of packaging, which consists of two types of packaging, namely: packaging PET plastic bottles (K1) and transparent glass bottles (K1). Each treatment was repeated twice, to obtain 16 experimental units. The results of the study until the 20th day storage were known, that the panelists' preference for color and aroma was in the range of 2.05 - 5.9. The test results on chemical quality variables: titrated total Acid range 0.512 % - 0.922 %, pH 2.10 - 2.26, Total Solid Soluble 220Brix - 250Brix and for Total Plate Count values of  9.1 x 103 - 4.7 x 105 CFU / ml.